The Kettlebell Lunge Clean exercise. Issue 4 (October 2018) - Henkin, Josh; Bento, Jessica; Liebenson, Craig
Abstract: Functional movements are designed to look at how our body functions in different environments. Power is often performed in the vertical plane and very stable positions of the body. Both life and sport require a great deal more complexity of movement with direction and deceleration playing key roles. The Kettlebell Lunge Clean (KLC) exercise is a safe and powerful exercise to teach these qualities and progress the power development and force absorption capabilities of the individual.